(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The republic owns a large reserve of natural resources. The high level of exploration of mineral deposits in Uzbekistan is associated with the extraction of fuel resources, precious, non-ferrous and rare metals, uranium ores, oil shale, and raw materials for construction materials. The article analyzes key ideas and related points shortly with examples.